Greening Up the Roof: a Study of Rooftop Spaces in Madison, Wisconsin - Radl, Margaret; Yang, Feier; Helms, Carly (My University, 2016)
The overall purpose of our study was to uncover the benefits and limitations of rooftop spaces in Madison, Wisconsin as well as a greater understanding in how these spaces are perceived and utilized by residents of Madison was gained. Our paper is split up into three sections: rooftop gardens, social spaces, and solar energy production. We conducted surveys and interviews to investigate current utilization of the rooftop areas in Madison. Despite limitations, those well versed in green roof implementation stress the benefits and importance of such spaces. Our findings have shown that while there is an increasing demand for green roof spaces in Madison, the city as a whole still has a large amount of available green space to expand out to. Future studies should focus on funding for green roof spaces and policy changes to help rooftops green spaces become mainstream.
Includes Photographs, Figures, Project designs/Blueprints, Graphs, Maps, Appendices and Bibliography.
Keywords: Madison, Wisconsin; Rooftop spaces; Rooftop gardens; Rooftop social spaces; Rooftop solar energy